2016
DOI: 10.1093/jxb/erw186
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the post-translational modification of multiple phosphoenolpyruvate carboxylase isoenzymes by phosphorylation and monoubiquitination during sorghum seed development and germination

Abstract: HighlightThis work documents the remarkable versatility and complexity of in vivo post-translational modifications (monoubiquitination and phosphorylation) of different plant-type phosphoenolpyruvate carboxylase (PEPC) isoenzymes during the life cycle of sorghum seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Indeed, degradation of both PEPC and PPCK by the polyubiquitin–proteasome pathway has been reported5960. Recently, monoubiquitination of PEPC during sorghum seed development and germination were also documented61. Additionally, the dephosphorylation of PEPC is catalyzed by PP2A1256.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, degradation of both PEPC and PPCK by the polyubiquitin–proteasome pathway has been reported5960. Recently, monoubiquitination of PEPC during sorghum seed development and germination were also documented61. Additionally, the dephosphorylation of PEPC is catalyzed by PP2A1256.…”
Section: Discussionmentioning
confidence: 98%
“…All PTPCs are subject to a light-dependent phosphorylation process involving an N -terminal regulatory serine that interacts with metabolite effectors, such as the feedback inhibitor L-malate, and the allosteric activator Glucose-6-phosphate (Glc-6P; Echevarria and Vidal, 2003). In addition, C 3 -type plant PEPCs have also been shown to be regulated by monoubiquitination (Uhrig et al, 2008; Shane et al, 2013; Ruiz-Ballesta et al, 2014, 2016), though this has not been demonstrated for the photosynthetic C 4 -PEPC to date (unpublished results).…”
Section: Introductionmentioning
confidence: 98%
“…Due to the key role that this enzyme plays in the C 4 pathway, the biochemical and signaling mechanisms controlling PEPC activity in the cytosol of leaf mesophyll cells have received significant research attention (Chollet et al, 1996; Echevarria and Vidal, 2003; Izui et al, 2004). In sorghum, PEPC belongs to a multigene family encoding five closely related plant-type PEPCs (PTPC; SbPEPC1-5) and one distantly related bacterial-type PEPC (BTPC) (Ruiz-Ballesta et al, 2016). Of the PTPCs, one family member, SbPEPC1, is an example of a C 4 photosynthetic PEPC, playing a functional role in C 4 and Crassulacean acid metabolism (CAM)-type photosynthesis, while the remaining four homologs, SbPEPC2-5, are C 3 PEPCs, that perform alternative functions in plants (O’Leary et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PEPC is subjected to different post-translational modifications (PTMs), such as phosphorylation, monoubiquitination, NO-related PTMs (S-nitrosylation, Tyr-nitration), and oxidative stress-associated PTMs (carbonylation) [ 9 , 10 , 11 , 12 , 13 ]. In addition, the acetylation of Arabidopsis PEPCs has recently been reported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%